ANALISIS YURIDIS TERHADAP TINDAK PIDANA PENELANTARAN ORANG DALAM LINGKUP RUMAH TANGGA (STUDI PUTUSAN NOMOR: 2062/PID.SUS/2018/PN-MDN) - MAURICE ROGERS; FANOTONA GIAWA; IRMA CESILIA SYARIFAH SIHOMBING; BERNADET INTAN WARUWU (LP2MTBM MAKARIOZ, 2020)
The abandonment of the household including unkind and disgraceful actions, in the public view of people's householdabandonment is assessed as having committed unpraiseworthy and socially sanctioned a penalty stamp to the perpetrators.The forms of the abandonment of the people in the household and its protection, i.e. not giving a living. One of theobligations of husband is to fulfill all the needs of the wife according to her ability which is expressly set out in article 34 ActNo. 1 year 1974 about marriage. Consideration of the Tribunal in the Judgment of the criminal act of the abandonment of thehousehold in the ruling number: 2062/PID.SUS/2018/PN-Mdn, to the defendant in accordance with the facts revealed in theproceedings such as the things that alleviate the defendant had not been punished, the defendant admitted and regretted hisdeeds.